CLINICAL IMMUNOLOGY AND ALLERGOLOGY AS AN IMPORTANT COMPONENT OF CONTINUOUS MEDICAL EDUCATION OF DOCTORS - Anna Havrylyuk; Svitlana Zubchenko; Valentyna Chopyak (Acta Medica Leopoliensia)
The science of clinical immunology and allergology is constantly developing. Every year, new opportunities open up in the fields of immuno-, allergy diagnostics, and immunotherapy. The teaching of these disciplines has been introduced in Ukrainian higher medical institutions for more than 25 years. However, the number of credits for these disciplines is, unfortunately, decreasing every year.